Probability of financial distress and proposed adoption of corporate governance structures: Evidence from Pakistan - Rabia luqman; Masood Ul hassan; Shanza Tabasum; Maria Shams Khakwani; Sadia Irshad (Cogent Business & Management, 2018)
This study examines the role of voluntary adoption of corporate governance mechanisms in mitigating the financial distress status of firms. Using the sample of 52 firms from non-financial sector listed at Karachi Stock Exchange and selecting time period of 10 years from 2006 to 2015, the study finds out the practices that are beneficial for firms and helps them in reducing the financial distress. Results of the study show that there is a negative significant relationship of blockholder ownership, director ownership and audit committee with the probability to financial distress. The causal relationship is also tested, and results show that voluntary adoption of corporate governance structures leads towards lower level of financial distress.
Keywords: 650